2017
DOI: 10.1038/s41598-017-00557-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide ameliorates chronic renal failure in rats by inhibiting apoptosis and inflammation through ROS/MAPK and NF-κB signaling pathways

Abstract: Chronic renal failure (CRF) is a major public health problem worldwide. Hydrogen sulfide (H2S) plays important roles in renal physiological and pathophysiological processes. However, whether H2S could protect against CRF in rats remains unclear. In this study, we found that H2S alleviated gentamicin-induced nephrotoxicity by reducing reactive oxygen species (ROS)-mediated apoptosis in normal rat kidney-52E cells. We demonstrated that H2S significantly improved the kidney structure and function of CRF rats. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 62 publications
7
74
0
1
Order By: Relevance
“…NF‐κB represents a cornerstone of the inflammatory process during nephrotoxicity that is activated in response to ROS . A recent study indicated that the expression of NF‐κB was upregulated in the kidney of rats administered gentamicin . This result is in accordance with our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…NF‐κB represents a cornerstone of the inflammatory process during nephrotoxicity that is activated in response to ROS . A recent study indicated that the expression of NF‐κB was upregulated in the kidney of rats administered gentamicin . This result is in accordance with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, ROS has been demonstrated to activate mitogen‐activated protein kinases (MAPK) pathway, which consecutively mediates apoptotic cell death . Some studies have shown that redox‐sensitive biological signaling agents, such as nuclear factor‐kappa B (NF‐κB) and its upstream‐related kinases including p38‐MAPK, as well as activation of apoptosis, are involved in nephrotoxicity caused by gentamicin .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, it has been widely accepted that a relatively high level of ROS causes redox imbalance, which induces cell apoptosis or necrosis under a wide variety of physiological and pathological conditions . Recent studies have proven that ROS can activate MAPKs, and apoptotic cell death induced by ROS is mediated by the p38MAPK pathway in lung and renal cells. Interestingly, in the kidney of CKD rats, the levels of ROS were markedly increased, the activities of anti‐oxidative enzymes, SOD and GSH‐Px, were significantly decreased, and ROS could induce apoptosis …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have proven that ROS can activate MAPKs, and apoptotic cell death induced by ROS is mediated by the p38MAPK pathway in lung and renal cells. Interestingly, in the kidney of CKD rats, the levels of ROS were markedly increased, the activities of anti‐oxidative enzymes, SOD and GSH‐Px, were significantly decreased, and ROS could induce apoptosis …”
Section: Introductionmentioning
confidence: 99%